FORMING CULTURE OF PROFESSIONAL AND LEGAL COMMUNICATION OF FUTURE LAWYERS IN THE COURSE OF PROFESSIONAL TRAINING AS A PEDAGOGICAL PROBLEM - Циганій, С. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2014)
The article presents some aspects of treating the process of forming the culture of professional and legal communication as a pedagogical problem. Attention is paid to the analysis of definitive system, the structure of professional and legal communication, the classification of its types